THE HISTORICAL BACKGROUND TO THE DEMOCRACY OF MODERN GEORGIA - Lili Amashukeli; Tamar Kiknadze (International Journal of Innovative Technologies in Social Science, 2022)
Georgia was a part of a totalitarian state for 70 years, but if we look back through its history, we find out that the conceptual foundations of the Georgian statehood had been prepared by the legacy of the public figures of previous epochs. The views of different historical periods and the legacy of the public figures conditioned the vector of the development of today’s Georgia and the respect for the democratic values. The article is about historical experience of Georgia which has an influence on the political life of modern country.